Islamic English in Maher Zain's songs: is there a need? - Othman, Khairiah; Abdul Malik, Faridah (American Scientific Publishers, 2017)
A significant rise in the number of English-speaking Muslims around the world calls for more attention on the proper usage of Islamic terms in the English language. Popularized by al-Faruqi, Islamic English refers to the English language modified to enable Muslims to carry Islamic proper names, nouns, meanings and concepts without distortion. This article aims to highlight the need for Islamic English to be used particularly for Muslims. The study employed content analysis method in examining Islamic terms and concepts utilized by Maher Zain in his English Islamic songs. The findings indicate the presence of Arabic words and concepts in his songs mainly due to the absence of equivalent English words, lack of accurate translation and a form of worship, hence the need for Islamic English. Keywords: Islamic English, Maher Zain, songs, World Englishes, varieties of English